Visual art experience and psychological distress among university students: parallel indirect effects through presence and search for meaning - Huanqin Lv (Frontiers in Public Health, 2026)
Purpose University students often experience academic pressure, interpersonal challenges, and uncertainty about future development, making psychological distress an important concern for health promotion in higher education. Visual art experience may provide opportunities for emotional expression, aesthetic immersion, self-reflection, and meaning-making. However, its association with psychological distress and the possible statistical indirect roles of presence of meaning and search for meaning remain insufficiently examined. This study therefore examined these associations in a cross-sectional university-student sample. Methods A cross-sectional online questionnaire survey was conducted within a single institutional context using non-probability online recruitment beginning on April 22, 2026. The analytic archive contained 500 submitted questionnaire records, of which 423 were retained after data-quality screening and 77 were excluded. Participants completed measures of visual art experience, presence of meaning, search for meaning, depressive symptoms, anxiety symptoms, and stress symptoms. Analyses included reliability and psychometric evaluation of the study-specific measures, Pearson correlations, hierarchical regression with assumption diagnostics, domain-specific outcome analyses, exploratory effect-modification tests, and a 5,000-resample bootstrap analysis of parallel indirect effects. Because no probability-sampling frame or invitation/start denominator was available, population representativeness and a conventional survey response rate are not claimed. Results Visual art experience was negatively associated with psychological distress ( r = −0.37, p < 0.001) and positively associated with both presence of meaning ( r = 0.62, p < 0.001) and search for meaning ( r = 0.12, p < 0.05). Presence of meaning was negatively associated with psychological distress ( r = −0.43, p < 0.001), whereas search for meaning was not significantly associated with psychological distress. In the primary parallel indirect-effect analysis, the indirect effect through presence of meaning was significant (95% bootstrap CI [−8.988, −4.151]), whereas the indirect effect through search for meaning was not significant (95% bootstrap CI [−0.490, 0.327]). Conclusion These findings provide preliminary cross-sectional evidence that visual art experience is associated with lower psychological distress among university students. The pattern of results is statistically consistent with an indirect pathway through presence of meaning, but it does not establish a causal psychological mechanism. Presence of meaning and search for meaning should be interpreted as distinct dimensions, and the findings should be understood as associations rather than causal effects.